The Contrastive Componential Analysis of the English Verb â€œto loveâ€ - Xenia, Tia (Universitas Sanata Dharma, 2019)
It has been commonly understood that a word is rich in synonyms; however if those synonymous words are analyzed comprehensively, it shows that they do not exactly denote the same meaning. In order to distinguish one meaning to the other meaning, the features of each synonym are classified to obtain the distinctive features. The aims of this study are to identify the distinctive features of the lexical items that are synonymous with the English verb â€œto loveâ€ and to explain the polysemy of that English verb. The English verb â€œto loveâ€ was taken as the object since it is a basic general English word that appears frequently in everyday contexts. To analyse the data, the researcher listed down the synonyms of â€œto loveâ€. After that, those synonyms were contrasted to obtain the distinctive features. By comparing the meanings of to love to the distinctive features obtained, the polysemy could be found and explained. This paper shows that there were sixteen synonymous verbs, 29 distinctive features that were classified into seven major features, and six polysemy of the English verb, to love.Keywords: meaning, componential analysisÂ